Respuesta :

Answer:

0 = 0

Step-by-step explanation:

Simplifying

7(x + -1y) = 7x + -7y

(x * 7 + -1y * 7) = 7x + -7y

(7x + -7y) = 7x + -7y

Add '-7x' to each side of the equation.

7x + -7x + -7y = 7x + -7x + -7y

Combine like terms: 7x + -7x = 0

0 + -7y = 7x + -7x + -7y

-7y = 7x + -7x + -7y

Combine like terms: 7x + -7x = 0

-7y = 0 + -7y

-7y = -7y

Add '7y' to each side of the equation.

-7y + 7y = -7y + 7y

Combine like terms: -7y + 7y = 0

0 = -7y + 7y

Combine like terms: -7y + 7y = 0

0 = 0

Solving

0 = 0

Answer:

Distributive Property

Step-by-step explanation:

When we're distributing something, there will always be a number or a variable is outside of a parenthisis signaling that you would need to multiply.

for Ex. 7(x-y), since there is a number that is connected to the outside of the parenthesis, that is a signal that we would need to multiply or distribute